Computational Statics and Dynamics An Introduction Based on the Finite Element Method - Öchsner, Andreas (Springer Nature Singapore : Imprint: Springer, 2016)
This book introduces readers to modern computational mechanics based on the finite element method. It helps students succeed in mechanics courses by showing them how to apply the fundamental knowledge they gained in the first years of their engineering education to more advanced topics. In order to deepen readers' understanding of the derived equations and theories, each chapter also includes supplementary problems. These problems start with fundamental knowledge questions on the theory presented in the chapter, followed by calculation problems. In total over 80 such calculation problems are provided, along with brief solutions for each. This book is especially designed to meet the needs of Australian students, reviewing the mathematics covered in their first two years at university. The 13-week course comprises three hours of lectures and two hours of tutorials per week.